Sound, space, and the city : civic performance in downtown Los Angeles - Peterson, Marina (City in the twenty-first century book series., 2010)
On summer nights on downtown Los Angeles's Bunker Hill, Grand Performances presents free public concerts for the people of the city. Marina Peterson explores the processes, from urban renewal to the performance of ethnicity and the experiences of audiences, through which civic space is created at downtown performances. Along with archival materials on urban planning and policy, Peterson draws extensively on her own participation with Grand Performances, ranging from working in an information booth answering questions about the artists and the venue, to observing concerts and concert-goers as an audience member, to performing onstage herself as a cellist with the daKAH Hip Hop orchestra. The book offers an exploration of intersecting concerns of urban residents and scholars today that include social relations and diversity, public space and civic life, privatization and suburbanization and economic and cultural globalization.